Epidemiology of obesity - Seidell, Jacob (Henry Stewart Talks, 2007)
Assessment of the national prevalence of obesity, Availability of good, updated data, Problems with the data, Important determinants of obesity in Europe: age, sex and social class (education/income), Obesity prevalence in adults, adolescents and children, Time-trends in obesity, Obesity in the WHO MONICA Study, Obesity prevalence varies widely within and between countries, The prevalence of childhood obesity is increasing at an alarming rate